Inovasi Pembelajaran Akidah Akhlak Menggunakan Contextual Teaching and Learning di MAN 1 Kendari - Siti Khairani Itsnainy; Syamsuddin; Nuryamin (Institut Kariman Wirayudha Sumenep, 2024)
This research aims to provide a clear and appropriate direction for the implementation of moral faith learning through the contextual teaching and learning model so that it can increase students' learning motivation. The character of students in the contemporary era demands learning innovations that accommodate their needs so that they can survive in the era of globalization. This study uses a type of qualitative research with primary data through interviews with teachers of moral beliefs in MAN 1 Kendari. Data is collected through observation, interview, and documentation techniques, then described, reduced, selected, and analyzed. The results of this study show that the innovation of learning moral beliefs in MAN 1 Kendari through the contextual teaching and learning model can activate students, provide learning through the process of acquiring and adding new insights that can encourage students to analyze every problem presented by the teacher so that they do not just memorize the material but reach the level of understanding and application in life on a daily basis. The learning of the contextual teaching and learning model in the subject of moral beliefs is organized through reflection journals, research projects, case studies, open-ended questions, and group discussions.